Birth Stories of Trinidad and Tobago: Sarah Mohammed - (:unkn) unknown (The University of the West Indies, 2024)
Sarah Mohammed is a first time mom from a small nuclear family and a large extended family. She recalls when she first learned that she was expecting and her decision to visit Mamatoto Resource and Birthing Centre.
Keywords: This resource is being hosted by the Campus Libraries at The University of the West Indies, St. Augustine Campus, Trinidad and Tobago. The content is to be used for non-commercial purposes to support teaching and research. The videos may be copied, distributed, and displayed verbatim. For commercial uses, you are required to seek permission from the copyright holder, email tammy.kremer@gmail.com.; Childbirth -- Trinidad and Tobago